Effect of Charcoal Particles on Thermophysiological Comfort Properties of Woven Fabrics. Issue 3 (4th March 2021) - Gunasekaran, G.; Prakash, C.; Periyasamy, S.
ABSTRACT: The objective of this study is to investigate the effect of the application of neem charcoal microparticles on thermophysiological comfort properties of the treated fabrics as against the control fabrics. The materials used for this study are 100% cotton, the synthetic woven fabrics and their blends such as 100% polyester and 65/35 polyester/cotton. The fabrics are pre-washed and are analyzed for the constructional parameters. The neem wood aged more than 5 years are collected and are used for preparation of neem charcoal particles using furnace heating method followed by ball milling. Characterization of the neem charcoal microparticles for particle size and distribution is carried out through Particle Analyzer. The presence of particles on the treated fabrics is confirmed through SEM study. Testing the untreated and treated fabrics for the thermophysiological properties such as wetting, wicking, water vapor permeability, air permeability, and thermal resistance by following the relevant standard test procedures were carried out.